CLINICAL AND HISTOPATHOLOGICAL CHARACTERISTICS AND SELECTED TREATMENT OUTCOMES OF MALIGNANT OCULAR SURFACE TUMORS IN 206 PATIENTS AT VIETNAM NATIONAL EYE HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and histopathological characteristics and selected treatment outcomes of three groups of malignant ocular surface tumors at Vietnam National Eye Hospital.Methods: This retrospective descriptive study with longitudinal follow-up included 206 patients with histopathologically confirmed squamous cell carcinoma, malignant melanoma, or conjunctival lymphoma who were treated at Vietnam National Eye Hospital between 2014 and 2023.Results: Squamous cell carcinoma was diagnosed in 129 patients (62.6%); corneal invasion occurred in 52.7%, orbital exenteration was performed in 8.5%, and suspected tumor-related death was recorded in 1.6%. Malignant melanoma was predominantly of the epithelioid cell type (57.9%), with a median follow-up of 44 months, an orbital exenteration rate of 31.6%, and a tumor-related or suspected tumor-related mortality rate of 44.7%. Most conjunctival lymphomas were low-grade tumors (74.4%); the median follow-up was 46 months, and mortality related to malignant lymphohematologic disease was 10.3%.Conclusion: Squamous cell carcinoma was the most common tumor group. Malignant melanoma was associated with high rates of orbital exenteration and tumor-related or suspected tumor-related mortality, whereas conjunctival lymphoma should be evaluated in the context of systemic lymphohematologic disease.
Keywords: malignant ocular surface tumor; squamous cell carcinoma; conjunctival melanoma; conjunctival lymphoma; orbital exenteration.